2015
DOI: 10.1210/jc.2014-2751
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Activation of Human Macrophages Is Rescued by Estrogen Treatment In Vitro and Impaired by Menopausal Status

Abstract: Estrogen treatment prevented LPS/IFN-γ action on human M2 macrophage markers and cytokine production, whereas menopausal estrogen loss was associated with an impaired response to alternative activation, suggesting that these mechanisms affect the cardiovascular risk profile in relation to menopausal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
73
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 41 publications
12
73
1
1
Order By: Relevance
“…Importantly, results obtained in the zymosan peritonitis model reveal that these mechanisms are maintained during an acute inflammation of the peritoneum. These results are in agreement with previous studies which suggested that estrogen is involved in macrophage activation and polarization in experimental models of inflammation424344 or in isolated macrophages/cell lines challenged with specific immune stimuli91545. Our study provides a major advancement to this knowledge as it proves estrogen to be per se a physiological regulator of the number and reactivity of peritoneal macrophages in intact healthy animals, in the absence of confounding factors such as recruited circulating monocytes achieved in wound healing or in different models of peritonitis.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, results obtained in the zymosan peritonitis model reveal that these mechanisms are maintained during an acute inflammation of the peritoneum. These results are in agreement with previous studies which suggested that estrogen is involved in macrophage activation and polarization in experimental models of inflammation424344 or in isolated macrophages/cell lines challenged with specific immune stimuli91545. Our study provides a major advancement to this knowledge as it proves estrogen to be per se a physiological regulator of the number and reactivity of peritoneal macrophages in intact healthy animals, in the absence of confounding factors such as recruited circulating monocytes achieved in wound healing or in different models of peritonitis.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro treatment of the BV2 microglial cell line with soluble estrogen did not induce an M2 phenotype, but rather reversed and limited the M1 phenotype induced by LPS. These results are similar to the work of Toniolo et al which reported that in vitro treatment with estrogen rescued the M2 phenotype after M1 polarization, but did not increase it over baseline expression (Toniolo et al, 2015). In addition, it was previously reported that the dampening of LPS-stimulated NO production in microglia by estrogen was mediated through estrogen receptor β (ERβ) (Baker et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…NO in saliva may be part of the non-specific natural defense mechanism of the oral cavity against pathogenic bacteria 38. Toniolo et al30 stated that menopause is associated with macrophage activation profiles skewed towards pro-inflammatory phenotype. Macrophages, which play a direct and important function in cell mediated immunity, contain peroxidase, several acid hydrolases and collagenases 39.…”
Section: Discussionmentioning
confidence: 99%